2010
DOI: 10.1080/02773810903259565
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Violet Radiation-Cured Biofiber Composites from Kenaf: The Effect of Montmorillonite on the Flexural and Impact Properties

Abstract: Biofiber composites, cured by ultra-violet (UV) radiation were produced using kenaf fibers as the reinforcing agent and unsaturated polyester as the matrix. This research work focused on the effects of the incorporation of kenaf fiber, montmorillonite (MMT), and cetyl trimethyl ammonium bromide-modified MMT (CTAB-MMT) in the unsaturated polyester composite. Overall, the incorporation of kenaf fibers in the form of mat had improved the flexural and impact properties of the composites. Addition of MMT into the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…According to Rozman et al 29 , the addition of MMT into the kenaf fiber-polyester system showed an improvement in flexural and impact properties up to 1% MMT. Further increase in the MMT loading had resulted in the decrease in these properties which was believed to be due to MMT agglomeration.…”
Section: Resultsmentioning
confidence: 99%
“…According to Rozman et al 29 , the addition of MMT into the kenaf fiber-polyester system showed an improvement in flexural and impact properties up to 1% MMT. Further increase in the MMT loading had resulted in the decrease in these properties which was believed to be due to MMT agglomeration.…”
Section: Resultsmentioning
confidence: 99%
“…Further addition led to agglomeration of MMT particles, causing a decrease in impact strength. 88 Literature study reveals that addition of biosynthesized alumina nanoparticles to hybrid banana/coir, sisal/coir, and sisal/banana biocomposites enhanced the impact strength by 9.65, 12.64, and 7.12%, respectively. 89 The addition of baggase ash particles to hybrid sisal/flax and sisal/kenaf biocomposites enhanced the impact strength.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of 1% of MMT into the kenaf fiber-polyester system showed improved impact properties. Further addition led to agglomeration of MMT particles, causing a decrease in impact strength . Literature study reveals that addition of biosynthesized alumina nanoparticles to hybrid banana/coir, sisal/coir, and sisal/banana biocomposites enhanced the impact strength by 9.65, 12.64, and 7.12%, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is in contrast with the works conducted before where the increase of lignocellulosic fibre in composite could result in increment of composite stiffness due to the inherent stiffness of the lignocellulosic fibre. [24][25][26] This is probably attributed by the degree of curing of the composites. As observed in Figure 1, the degree of curing decreases as the kenaf fibre content is increased due the degree of UV radiation penetration.…”
Section: Resultsmentioning
confidence: 99%